PENGARUH PERENCANAAN DAN IMPLEMENTASI TERHADAP REALISASI ANGGARAN DENGAN KEBIJAKAN PERUBAHAN ANGGARAN SEBAGAI VARIABEL INTERVENING PADA DINAS KESEHATAN KOTA KUPANG - Mbado, Margarethy Rohanie; Mbate, Maromi Merlin (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2022)
The Kupang City Health Office is an accounting entity from the Kupang City Government which is obliged to carry out accounting and accountability reports for the implementation of the Regional Revenue and Expenditure Budget by compiling financial reports in the form of Budget Realization Reports (LRA), Balance Sheets, and Notes to Financial Statements abbreviated as CALK. This type of research is quantitative using the SEM-PLS analysis tool. The informants in this study were employees who work in the Health Department of Kupang City. The results showed that The results of the descriptive analysis of all the variables in this research were in the good category, so that the management of the Health Department needed to maintain the system that was already running and they needed to improve their work performance so that in the future it could be even better, Planning variable significantly influence with the budget policies variable of the Health Department of Kupang City, The planning variable does not significantly influence the budget realization variable, The implementation variable has a significant influence with the budget policies variable, The implementation variable does not significantly influence the budget realization variable, Budget policies variable significantly influence budget realization variable, Budget planning variable indirectly through budget policies has a significant influence on budget realization, Budget implementation variable indirectly through the budget policies significantly influence the budget realization. Based on the results of this research, it is suggested that in running the plan, the Health Department of Kupang City should use achievement data as the estimate and the budget in planning needs to be increased, in the budget implementation of Health Department of Kupang City it is important to pay attention about coordination in the inclusion of APBD draft documents so that budget discipline can run properly, related to the budget realization of the Health Department of Kupang City, it should pay more attention to activities that involve many people